Dual plasmonically tunable slow light based on plasmon-induced transparency in planar graphene ribbon metamaterials. Issue 40 (8th October 2018) - Xu, Hui; Zhao, Mingzhuo; Xiong, Cuixiu; Zhang, Baihui; Zheng, Mingfei; Zeng, Jianping; Xia, Hui; Li, Hongjian
Abstract : We can achieve a very obvious dual plasmon induced transparency effect and obtain a good slow light property. Abstract : We propose a simulated terahertz design based on planar graphene ribbons. With numerical simulation, we can achieve a very obvious dual plasmon-induced transparency phenomenon through the destructive interference in this structure. Moreover, due to the simple design of this structure and the complete continuous graphene ribbons, the Fermi level of graphene can be regulated by voltage. Thus, the dual plasmon-induced transparency phenomenon can be easily tuned in the numerical simulation. Further structural analysis shows that the two graphene chips on the side of the graphene ribbons play a crucial role in the dual plasmon-induced transparency phenomenon. As the length of the two chips is close, the dual plasmon-induced transparency phenomenon gradually becomes a single plasmon-induced transparency phenomenon. The theoretical analysis of this structure shows that this system has a very high group index, and its maximum value is 800, which is far greater than that of other types of slow light devices. This work may open up a new way for designing tunable terahertz graphene-based devices and slow light devices.